A new cyclohexapeptide, penitropeptide and a new polyketide, penitropone from the endophytic fungus Penicillium tropicum. Issue 27 (6th July 2016) - Zeng, Yanbo; Wang, Hao; Kamdem, Ramsay S.T.; Orfali, Raha S.; Dai, Haofu; Makhloufi, Gamall; Janiak, Christoph; Liu, Zhen; Proksch, Peter
Graphical abstract: Highlights: Four secondary metabolites were obtained during the first chemical examination of endophytic fungus Penicillium tropicum . One new cyclohexapeptide, namely penitropeptide, of which the absolute configuration was determined using Marfey's method. One new polyketide derivative, penitropone whose stereostructure was confirmed by single crystal X-ray diffraction. Abstract: The first chemical investigation of the endophytic fungus Penicillium tropicum isolated from leaves of Sapium ellipticum afforded a new cyclohexapeptide, penitropeptide (1 ), and a new polyketide, penitropone (2 ), in addition to two known compounds, 6-hydroxy-8-methoxy-3 S, 5-dimethyl-3, 4-isocoumarin (3 ) and adametizine B (4 ). Their structures were unambiguously elucidated on the basis of 1D and 2D NMR spectroscopy as well as mass spectrometry, and by comparison with the literature. The absolute configurations of these two new compounds1 and2 were determined by Marfey's method and X-ray single crystal diffraction, respectively. All isolated compounds were tested for their cytotoxic and antibacterial activities. However, none of them showed significant activity.